2009
DOI: 10.1007/s12284-009-9029-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers for Sweet Sorghum Based on Microarray Expression Data

Abstract: Using an Affymetrix sugarcane genechip, we previously identified 154 genes differentially expressed between grain and sweet sorghum. Although many of these genes have functions related to sugar and cell wall metabolism, dissection of the trait requires genetic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Our comparative analysis from re-sequencing data showed that genes with functionally divergent genes between BT×623 and Keller might not be directly involved in sugar accumulation. Interestingly, screening of sorghum genes linked to high sugar content indicated that 80% of differentially expressed genes between sweet and grain sorghum had their orthologs in rice suggesting limited contribution of their gene content for differentiating sorghum sugar accumulation [8,9]. Thus, our data and others [8,9,28] suggested that expression divergence should play important roles in the divergence of sugar accumulation between sweet and grain sorghum lines.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Our comparative analysis from re-sequencing data showed that genes with functionally divergent genes between BT×623 and Keller might not be directly involved in sugar accumulation. Interestingly, screening of sorghum genes linked to high sugar content indicated that 80% of differentially expressed genes between sweet and grain sorghum had their orthologs in rice suggesting limited contribution of their gene content for differentiating sorghum sugar accumulation [8,9]. Thus, our data and others [8,9,28] suggested that expression divergence should play important roles in the divergence of sugar accumulation between sweet and grain sorghum lines.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, screening of sorghum genes linked to high sugar content indicated that 80% of differentially expressed genes between sweet and grain sorghum had their orthologs in rice suggesting limited contribution of their gene content for differentiating sorghum sugar accumulation [8,9]. Thus, our data and others [8,9,28] suggested that expression divergence should play important roles in the divergence of sugar accumulation between sweet and grain sorghum lines. In fact, changes of gene expression in eukaryotes often give rise to new phenotypes and the changes were frequently used as a proxy indicator of functional divergence of genes [29].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The juice from three internodes of the main stem was harvested at the time of flowering and the Brix degree measured as previously described [30,31]. The average Brix degree from three internodes per plant was used.…”
Section: Methodsmentioning
confidence: 99%
“…We discovered allelic variation in miR169 expression between grain and sweet sorghum, suggesting that miR169 could also play a role in the sugar content of sorghum stems (Calvino et al 2011). Although high sugar content in stems is a trait shared by sorghum and sugarcane (Calvino et al 2008, 2009), this trait seems to be silent in other grasses (Calvino and Messing 2011). This prompted us to investigate the evolution and dynamic amplification of miR169 gene copies in grass genomes.…”
Section: Introductionmentioning
confidence: 99%